Double-stranded cucumovirus associated RNA 5: which sequence variations may be detected by optical melting and temperature-gradient gel electrophoresis? - Steger, G (1987)
Sequence variants of the double-stranded form of satellite RNAs of cucumber mosaic virus (dsCARNA 5) were analyzed for the possibility to experimentally detect minor nucleotide sequence changes. Denaturation maps (helix-probability versus position of the nucleotide in the sequence versus temperature) were calculated applying the Poland algorithm. Optical denaturation curves and temperature-gradient gel mobility curves were simulated using the denaturation maps and were compared with experimental results from optical melting and temperature-gradient gel electrophoresis (Tien Po et al., accompanying paper). Melting of the dsRNAs starts from both ends of the molecule in two transitions of low co-operativity, continues in the right part in a highly co-operative transition, and is finished in another highly co-operative transition including strand-separation. Whereas all parts of the molecule contribute uniformly to the optical melting curve, opening of the ends predominates in the retardation transition in gel electrophoresis. Detailed discussion of the influence of base pair changes in the sequence shows that a single base pair change may be detected by temperature-gradient gel electrophoresis, if it is located in certain favorable locations, whereas its detection in optical melting curves is possible only in very special cases. The systematic differences found in the accompanying paper between necrogenic and non-necrogenic dsCARNA 5 could be interpreted on the basis of such nucleotide sequence differences.